2019
DOI: 10.1159/000496809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Mesenchymal Stromal Cells in the Treatment of Acute Graft-versus-Host Disease

Abstract: Acute graft-versus-host disease (aGvHD) continues to impact morbidity and mortality after allogeneic stem cell transplantation (allo-SCT). First-line therapy for aGvHD still remains the use of high-dose corticosteroids. Unfortunately, 40–60% of patients with aGvHD exhibit steroid resistance, which is associated with a very poor prognosis. As no effective second-line therapy existed, in recent decades various treatment options were considered for the treatment of therapy-refractory GvHD. Based on their in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 39 publications
(77 reference statements)
3
57
0
7
Order By: Relevance
“…Studies have shown that providers do not tightly adhere to recommended dosing of GVHD with an average dose of 1.4 × 10 6 MSCs/kg and three total doses administered (range is 1-10 doses administered) [16]. With such varying doses in MSC treatments, adverse events might be expected in the comparatively higher-dosed infusion; but overall, studies have not shown signi cant adverse events, which is consistent with our observations [15][16]. There has been…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shown that providers do not tightly adhere to recommended dosing of GVHD with an average dose of 1.4 × 10 6 MSCs/kg and three total doses administered (range is 1-10 doses administered) [16]. With such varying doses in MSC treatments, adverse events might be expected in the comparatively higher-dosed infusion; but overall, studies have not shown signi cant adverse events, which is consistent with our observations [15][16]. There has been…”
Section: Discussionsupporting
confidence: 85%
“…The approval emanated from a Phase III trial reporting that Darvadstrocel led to 50% combined remission, which was maintained after 1 year of treatment, in comparison with 34% in the control arm (Panés et al, 2016(Panés et al, , 2018Panes et al, 2017). Interestingly, several "orphan designation" approvals were granted by the European commission according to certain guidelines for the use of human MSCs in the treatment of GvHD, thromboangiitis obliterans (Buerger disease), and ALS (Yu et al, 2018 According to their study, the effectiveness of MSC-FFM is due to donor selection in addition to strict collection and preparation processes (Bader et al, 2018), which yield adequate doses of MSCs with high batch-to-batch consistency (Elgaz et al, 2019). The distinguished data on MSC-FFM clearly elucidate the reasons behind the discrepancies (different survival rates and response levels to allogeneic MSC) and failures of other phase III clinical trials (Galipeau, 2013;Galipeau and Sensébé, 2018).…”
Section: Immune-based Disordersmentioning
confidence: 99%
“…Isolated studies reported serum biomarkers of GVHD severity including IL-2, tumor necrosis factor receptor 1 (TNFR1), regenerating islet-derived protein 3 alpha (Reg3a), and levels of inflammatory cytokines, which not clearly correlate with the response in humans. More studies are needed to obtain correlative research data [94,95]. This outcome results in the first Food and Drug Administration (FDA) approved MSCs product in the United States [96,97].…”
Section: Msc Use In Clinical Studies 61 Clinical Potential and Markementioning
confidence: 99%